Manganese deficiency or dietary manganese(III) oxide nanoparticle supplementation: consequences for hematology, and intestinal and brain immunity in rats - Różaniecka-Zwolińska, Karolina; Cholewińska, Ewelina; Fotschki, Bartosz; Juśkiewicz, Jerzy; Ognik, Katarzyna (Frontiers in Immunology, 2025)
IntroductionThe study aimed to determine the effect of manganese (Mn) exclusion from the mineral mixture added to the rat diet and replacing the recommended level of MnCO3 (65 mg Mn/kg diet) with Mn2O3 nanoparticles (Mn2O3NPs) in the diet on blood hematology and selected immunological indices of the blood, jejunum, and brain.MethodsThe experiment was conducted on twenty-four, Wistar rats divided into 3 equal groups. The control (K) group received a diet containing 65 mg/kg of additional Mn originating from the mineral mixture), group B (negative control) was fed a diet deprived of Mn from the mineral mixture, and group N was fed a diet containing 65 mg/kg Mn from Mn2O3NPs preparation. All rats received the experimental diets for 12 weeks. At the end of the experiment, samples of blood, jejunum, and brain were collected from all rats from each group.ResultsMn exclusion from the rat diet led to anemia, worsened the body’s immune response, and caused systemic and local inflammation as indicated e.g. by decreased RBC, HCT, and the level of HGB, and CRP in blood, CRP and IgA in the jejunum, and IgG in the brain as well as an increased level of IL-2, IgG and TNF-α in blood, and IL-6 in jejunum. In turn, replacing the recommended level of MnCO3 with Mn2O3NPs in the rat diet worsened the immune response and caused local inflammation in the brain as indicated by an increase in TNF-α level and Cp activity, as well as decreased levels of IgG. Analogical changes were not observed in the jejunum or systemic level.DiscussionThe obtained results may suggest that the body has activated adaptive mechanisms that efficiently limit the spread of immune system disorders throughout the body.